Reducing the Ambiguity in Translating Prepositions from English into Arabic - Alnasery, Israa Hamid Shnain (Arts for Linguistic & Literary Studies, 2024)
The study seeks to identify the common difficulties and ambiguities that arise when translating prepositions from English into Arabic and to provide suggestions for improving the precision and understandability of this process. Data are collected from a wide range of online translations carried out by translators with varying degrees of training and proficiency. The findings of a study have highlighted the importance of considering the intricate details of the target language and its cultural background while translating prepositions. The study suggests that linguistic and cultural variations can lead to difficulties when translating idiomatic statements that contain prepositions. Prepositional idioms, which are commonly used in informal English, can be particularly challenging to translate accurately in other languages. The study suggests that language proficiency alone is insufficient for accurate translation. Translators must also take into account cultural and emotional nuances while translating prepositions to ensure that the intended meaning is conveyed accurately.